Analisis Iklan Sosial Media Tiktok, Brand Image dan Kepuasan Konsumen terhadap Minat Beli Produk COSRX - Putri, Fani Aprilia; Hariasih, Misti (Universitas Batanghari, 2024)
This research aims to determine the influence of the Tiktok Social Media Advertising Variables, Brand Image, Cunsumer Satisfaction on Interst in Buying COSRX Products. The method used ini descriptive qunatitative research, sampling in this study used Random Sampling with a sample size of 100 respondents. Data collection uses questionnaires. The tests in this research carried out Validity test, Rehabilitation Test, Normality Test, Linearity Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Test,T Test, F Test, Determination Coefficient Test (R2). The research results of Tiktok Social Media Advertising have no and significant influence on Purchase Interest, Brand Image have no and significant influence on Purchase Interest, Cusumer Satisfaction has a positive and significant influence on Purchase Interest.